V. P. TSESEVICH AND MOSCOW VARIABLE-STAR ASTRONOMERS - Samus, N. N. (Одеські астрономічні публікації, 2007)
This paper is a brief account of the variety of ties between V.P. Tsesevich and the Moscow variable-star team: publications in co-authorship (mainly in the form of collective monographs), Tsesevich's work in the Moscow plate stacks, conferences, Tsesevich's contribution to the General Catalogue of Variable Stars, etc.